The Influence of Interest Rates, Exchange Rates, and Gold Prices on the Jakarta Islamic Index - Baihaqqy, Mochammad Rizaldy Insan; Ikhsan, Sugiyanto (Jurnal Ilmiah Akuntansi Kesatuan, 2026)
The background of this study is global and domestic economic volatility that impacts the performance of the Islamic capital market in Indonesia. The Jakarta Islamic Index, as one of the main indicators of Islamic stocks, reflects the stability and resilience of sharia-based investment instruments. This study emphasizes novelty through the use of 13 years of long-term annual data and focuses on the relationship between conventional macroeconomic indicators and gold prices as an alternative investment asset with the Islamic stock index. This study aims to analyze the influence of interest rates, exchange rates, and gold prices on the Jakarta Islamic Index during the 2010–2022 period. The method used is quantitative with multiple linear regression, where the Jakarta Islamic Index acts as the dependent variable, while the Bank Indonesia policy interest rate, the IDR exchange rate against the USD, and the price of gold per gram serve as independent variables. The results show that interest rates and gold prices have a negative effect on the Jakarta Islamic Index, while the exchange rate has a positive effect. These findings confirm that interest rate and exchange rate stability are important for strengthening the competitiveness of the Islamic capital market in Indonesia.